STUDIES ON THROMBOLYTIC AND ANTI-HELMINTIC ACTIVITY OF Cocccinea grandis - B Deepti (Indonesian Journal of Pharmacy, 2014)
Traditional system of medicine consists of large number of plants with various medicinal and pharmacological values and hence represents a priceless tank of new bio active molecules. Coccinea grandis belongs to the family Cucurbitaceae, is a rapidly growing, perennial climber or trailing vine. Traditionally different parts of this plant namely roots, leaves, and fruits are used in folklore medicine for several purposes like jaundice, diabetes, wound healing, ulcers, stomach ache, skin disease, fever, asthma, cough. Development of anthelmintic resistance and high cost of conventional anthelmintic drugs led to the evaluation of medicinal plants as an alternative source of anthelmintics.  As no scientific data was available on this plant hence, the present study was carried out for the investigation of antihelmintic activity and thrombolytic activity of bark of Coccinea grandis. Antihelmintic activity was done on pheritima posthuma. The results obtained were compared with standard albendazole and control groups respectively, the parameters evaluated are time of paralysis and time of death. On the other hand thrombolytic activity was done by using aqueous extract of Coccinea grandis bark. Thrombi or emboli can lodge in a blood vessel and block the flow of blood in that location depriving tissues of normal blood flow and oxygen. This can result in damage, destruction (infarction), or even death of the tissues (necrosis) in that area. Streptokinase is an antigenic thrombolytic agent used for the treatment of acute myocardial infarction, served as standard. This study was conducted on human blood sample and compared with standard and control groups respectively. The parameters studied are percentage of clot lysis. From the present study we found that various extracts of this plants showed significant thrombolytic and antihelmintic properties.Key words: thrombolysis, helminthes, coccinea, albendazole, streptokinase.